A quantitative analysis of doctoral dissertations in communication in mainland China. Issue 6 (2nd November 2021) - Chen, Lijuan; Wei, Yuruo; Zhang, Guoliang
ABSTRACT: Doctoral candidates are the important fundament and potential of any given discipline. Their doctoral dissertations are not only a valuable academic resource, but also a barometer of the development of a discipline that should not be overlooked. This research adopts a quantitative method from the perspective of bibliometric analysis. We reviewed the research topics, methods and theoretical basis of the communication doctoral dissertations ( n  = 487) in a sample of eight selected universities in mainland China from 2001 to 2018. The result shows that these dissertations have an extensive topic preference and gradually formed a more distinct research paradigm, while critical thinking and a deeper exploration of theory still need to be cultivated.